Term histologic chorioamnionitis: a heterogeneous condition. (May 2015) - Conti, Nathalie; Torricelli, Michela; Voltolini, Chiara; Vannuccini, Silvia; Clifton, Vicky L.; Bloise, Enrico; Petraglia, Felice
Abstract: A histologic response of histologic chorioamnionitis (HCA) is defined as an intrauterine inflammatory condition characterized by acute granulocyte infiltratration into the fetal–maternal or the fetal tissues. Prevalence of HCA is inversely correlated with gestational age, occurring in 50% of preterm birth and in up to 20% of deliveries at term. Regardless of these standard definitions, understanding HCA is challenging as it reflects a heterogeneous condition. A histologic response of HCA from term placentas often does not correspond to a clinical presentation; in this context, the present review aims to analyze main characteristics of this condition, in particular focusing on mechanisms and birth outcomes.